Variation and response to experimental warming in a New Zealand cushion plant species. (7th April 2015) - Cranston, Brittany H.; Monks, Adrian; Whigham, Peter A.; Dickinson, Katharine J. M.
Abstract Cold adapted plants, such as cushion plants, may be particularly sensitive to climate warming because of their compact growth form and high branch density. In the oceanic southern hemisphere, cushion communities tend to have large range distributions at low latitudes (sea level to low alpine), thus providing an opportunity to test the effects of temperature on plant morphology and reproduction across gradients. Using Donatia novae‐zelandiae as a model species, we compared the leaf morphology, reproduction and responses to warming. Two low‐alpine sites (Maungatua (880 m a.s.l.), Blue Mountains (1000 m a.s.l.)) and two sea‐level sites (Waituna 1 (0 m a.s.l.), Waituna 2 (0 m a.s.l.)) in South Island, New Zealand were used. Donatia novae‐zelandiae cushions differed significantly between the high‐elevation and sea‐level sites both morphologically and in terms of reproduction. High‐elevation cushions produced more flowers (threefold more flowers per plant) and seeds (sevenfold more seeds per capsule) than at sea level, but leaves were larger at sea level (in length and specific leaf area). The cushions were also twice as compact at the high‐elevation sites. After two growing seasons of artificial warming, seed production (35%), leaf length (7%) and width (13%), and specific leaf area (63%) significantly decreased in D. novae‐zelandiae plants; flower production was not significantly affected. Cushion plant morphology and reproduction were significantly affected by environmental drivers at their establishment sites, but all populations responded negatively to artificial warming of 1–3°C. Many cushion plants are considered keystone species because of their propensity to facilitate the growth and establishment of other plant species, the inferred negative effects of global warming on cushion plant species may have a cascading effect on other alpine plant groups.